2018
DOI: 10.3233/hab-180345
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies prevalence against Haemophilus influenzae type b in Jeddah population, Saudi Arabia. III. Antibodies avidity

Abstract: Our previous results showed higher level of anti-Hib IgG (2.41 μg/ml) average geometric mean concentration (GMC) regardless of age and gender, followed by levels of IgM (0.91 μg/ml) and IgA (0.34 μg/ml), reflecting the prevalence of immunity against Hib. Current study was evaluated the avidity profile for these high anti-Hib concentration. The IgM avidity analysis did not revealed any significant results between male and female values. While, the average of IgA avidity in male samples were significantly (P< 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, we did find that the level of IgG2 subclass was significantly higher in patients who survived the disease compared to those who did not. Previous studies demonstrated that the IgG2 level was associated with protective immunity (Zarei and Redwan, 2019) and defense against recurrence of capsulated bacterial infections (Kralickova et al, 2017;Yamazaki et al, 2019). Follow up work includes a comparison between the intracellular bacterial growth rate of live B. ps pre-opsonized with purified IgG2 antibodies derived from survivors and nonsurvivors.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did find that the level of IgG2 subclass was significantly higher in patients who survived the disease compared to those who did not. Previous studies demonstrated that the IgG2 level was associated with protective immunity (Zarei and Redwan, 2019) and defense against recurrence of capsulated bacterial infections (Kralickova et al, 2017;Yamazaki et al, 2019). Follow up work includes a comparison between the intracellular bacterial growth rate of live B. ps pre-opsonized with purified IgG2 antibodies derived from survivors and nonsurvivors.…”
Section: Discussionmentioning
confidence: 99%